(untitled) (Journal of Engineering, 2015)
This research presents a study in ultra-desulfurization of diesel fuel produced from conventional hydro desulfurization process, using oxidation and solvent extraction techniques. Dibenzothiophene (DBT) was the organosulfur compound that had been detected in sulfur removal. The oxidation process used hydrogen peroxide as an oxidant and acetic acid as homogeneous catalyst . The solvent extraction process used acetonitrile (ACN) and N-methyl – 2 - pyrrolidone (NMP) as extractants . Also the effect of five parameters (stirring speed :150 , 250 , 350 , and 450) rpm, temperature (30 , 40 , 45 , and 50) oC, oxidant/simulated diesel fuel ratio (0.5 , 0.75 , 1 , and 1.5) , catalyst/oxidant ratio(0.125,0.25,0.5,and0.75) , and solvent/simulated diesel fuel ratio(0.5,0.6,0.75,and1) were examined as well as solvent type. The results exhibit that the highest removal of sulfur is 98.5% using NMP solvent while it is 95.8% for ACN solvent. The set of conditions that show the highest sulfur removal is: stirring speed of 350 rpm , temperature 50oC , oxidant/simulated diesel fuel ratio 1 , catalyst/oxidant ratio 0.5 , solvent/simulated diesel fuel ratio 1. These best conditions were applied upon real diesel fuel (produced from Al-Dora refinery)with 1000 ppm sulfur content . It was found that sulfur removal was 64.4% using ACN solvent and 75% using NMP solvent.